Knowing the Unknown: The Dynamic Role of Intellectual Capital on Firm’s Performance (Journal of Asian Development Studies, 2025)
This paper analyses the relationship between Intellectual Capital and its components and the financial performance of the firms. Modified Value-Added Intellectual Capital (MVAIC) model has been employed to calculate the Intellectual Capital. To measure financial performance, the proxy return on assets (ROA) has been utilized. The relationship between Intellectual Capital and financial performance has been explored by considering non-financial listed companies of the Pakistan Stock Exchange. This paper investigates data ranging from 2010 to 2024. Autoregressive Distributed Lag (ARDL) Model has been applied to better understand the relationship. The outcomes of this paper reveal a strong association between Intellectual Capital and financial performance in the short and long run. Moreover, the components of Intellectual Capital, such as human, structural, relational, and employed capital, also showed a strong association with financial performance in both the short and long run.